(untitled) (International journal of medical sciences, 2026)
Background: Global migration dynamics have highlighted significant health disparities among vulnerable populations, particularly children of migrant workers. These children frequently experience higher rates of preventable acute illnesses, delayed immunizations, and poor nutritional outcomes. A hypothesized root cause of this vulnerability is the inadequate health literacy of their parents, compounded by language and cultural barriers. Objective: To evaluate the impact of a targeted educational intervention designed to improve the health literacy of migrant parents on the subsequent risk and incidence of preventable illnesses in their children. Methods: A prospective, interventional cohort study was conducted involving 88 migrant families with at least one child under the age of 7. The families were divided into an Intervention Group (n=45), which received a structured, culturally adapted, 3-month health literacy program, and a Control Group (n=43), which received standard pediatric outpatient care. Parental health literacy was measured using the Short Assessment of Health Literacy (SAHL) tool at baseline and at 6 months post-intervention. Pediatric health outcomes (incidence of acute respiratory and gastrointestinal infections, and vaccination adherence) were tracked over a 12-month period. Results: At baseline, inadequate health literacy was prevalent in both groups (over 65%). Following the educational intervention, the Intervention Group demonstrated a significant increase in health literacy scores (from 14.2 ± 3.1 to 24.5 ± 2.4 points, p < 0.01). Concurrently, the incidence of acute pediatric illnesses in this group decreased by 42% over the 12-month follow-up compared to the previous year. Furthermore, vaccination compliance in the Intervention Group reached 95.5%, significantly higher than the 76.7% observed in the Control Group (p < 0.05). Conclusion: There is a direct, modifiable link between parental health literacy and pediatric health outcomes in migrant populations. Implementing culturally sensitive educational interventions for migrant parents effectively bridges the health equity gap, significantly reducing the risk of preventable diseases in their children.